Clinicopathological study of anemia during pregnancy - C., Sarojamma; Subiksha, R. Atchutha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: In developing countries the prevalence of anemia among pregnant women averages 60% resulting in varying levels of adverse pregnancy outcomes. Iron, Vitamin B12 and folic acid deficiencies, malaria, intestinal parasitic infections and hemoglobinopathies are the principal causes of anemia in pregnancy. Above nutritional requirements increase during pregnancy and if it is not maintained, may result in adverse maternal and fetal outcomes. The aim of this study was to study the prevalence of anemia in pregnant mothers, study the clinical patterns of anemia in pregnancy and to study the histopathological patterns of anemia during pregnancy. Methods: This is a prospective study done on 60 pregnant women whose hemoglobin level is less than 10.9 gm/dL. Blood samples were taken, and peripheral blood smears were examined along with their complete clinical and obstetric history. Results: Out of 60 cases of anemia, 40% were found to have dimorphic anemia, 30% with microscopic hypochromic anemia, 20% of patients have normocytic hypochromic anemia, 1.7% had sickle-cell anemia and 8.3% of patients were thalassemia cases. The risk factors for anemia in this study is noted to be low social economic status, occurrence of complications during previous pregnancy and multiparty. In this study anemia was more commonly found in the multigravida women and in the third trimester of pregnancy. Conclusions: With improved social economic conditions, early detection, good antenatal care, awareness regarding available treatment, a healthy diet, routine antenatal counselling and adequate iron supplementation, anemia in pregnancy can be avoided.